HYDROCHEMICAL CHARACTERISTICS AND GEOTHERMOMETRY APPLICATIONS OF HOT GROUNDWATER IN EDIPSOS AREA, NW EUBOEA (EVIA), GREECE - Kanellopoulos, C.; Christopoulou, M.; Xenakis, M.; Vakalopoulos, P. (Bulletin of the Geological Society of Greece, 2016)
In Edipsos area many hot springs occur, as a result of both active tectonic of the area and recent volcanism (Lichades volcanic center). A geochemical study of Edipsos hot groundwaters was undertaken, in order to assess the hydrochemistry of hot springs from Edipsos and re-evaluate the geothermal situation of the area. For that purpose, 12 water samples were collected and analyzed by Spectrophotometry for the main ions and by AAS, ICP-OES and ICP-MS for major and trace elements. The interpretation of the analytical data showed that the geochemistry of Edipsos hot groundwaters is controlled by three factors i) a deep magmatic source, ii) the chemical composition of the local rocks (ultramafic and carbonates) and iii) sea water. The application of chemical geothermometers is problematic because of the chemical composition of the hot groundwaters and especially the high participation of the sea water. The temperature which derives from the use of Na-K-Ca geothermometer is greater than 160°C. Although, several studies have conducted in the area still remain unanswered questions concerning the underground circulation of the hot groundwater, in which only deep drilling data could give answers.